No winners here tonight: race, politics and geography in one of the country's busiest death penalty states - Welsh-Huggins, Andrew (Ohio University Press series on law, society and politics in the Midwest, 2009)
Early justice -- A new law -- The volunteer -- The role of race -- The bargaining of death -- Geography as judge -- Diminishing mercy -- Last day -- Freakish or fair -- The future